The combined action of omega-3 polyunsaturated fatty acids and grape proanthocyanidins on a rat model of diet-induced metabolic alterations. Issue 8 (15th July 2016) - Ramos-Romero, Sara; Molinar-Toribio, Eunice; Pérez-Jiménez, Jara; Taltavull, Núria; Dasilva, Gabriel; Romeu, Marta; Medina, Isabel; Torres, Josep Lluís
Abstract : A combination of ω-3 PUFAs (EPA/DHA 1 : 1) and proanthocyanidins reverts metabolic changes induced by an energy-dense diet, more effectively than either supplement individually. Abstract : It has been suggested that food components such as ω-3 polyunsaturated fatty acids (ω-3 PUFAs) and (poly)phenols counteract diet-induced metabolic alterations by common or complementary mechanisms. To examine the effects of a combination of ω-3 PUFAs and (poly)phenols on such alterations, adult Wistar-Kyoto rats were fed an obesogenic high-fat high-sucrose diet supplemented, or not, for 24 weeks with: eicosapentaenoic acid (EPA)/docosahexaenoic acid (DHA) 1 : 1 (16.6 g kg −1 feed); proanthocyanidin-rich grape seed extract (GSE, 0.8 g kg −1 feed); or EPA/DHA 1 : 1 + GSE. Body weight, feed intake, and plasma glucose were evaluated every 6 weeks, while adipose tissue weight, insulin, glucagon, ghrelin, leptin, adiponectin, cholesterol, and triglycerides were evaluated at the end of the experiment. ω-3 PUFAs reduced plasma leptin and cholesterol levels, but did not modify diet-induced perigonadal fat or plasma insulin levels; while GSE increased plasma triglyceride levels. The combined action of ω-3 PUFAs and the proanthocyanidins reduced plasma insulin and leptin, as well as partially prevented perigonadal fat accumulation. While separate supplementation with ω-3 PUFAs or grape proanthocyanidins may not counteract all the key metabolic changes induced by a high-energy-dense diet, the combination of both supplements reverts altered insulin, leptin and triglyceride levels to normal.